302 A PROSPECTIVE MODEL OF OSTEOARTHRITIS: COMPARATIVE IMAGING OF THE KNEE IN MICE WITH OSTEOGENESIS IMPERFECTA. (1st January 2005) - Watts, C. E.; Blair, J.; Morris, D.; Schimel, D.; Marini, J.
Abstract : Osteoarthritis (OA) has long been recognized as a disease of the articular cartilage, but the role of subchondral bone is poorly understood in this disease process. Currently, our understanding of the sequence of events leading to a compromise of the joint in OA is rather limited. In this study, we propse to use an animal model of Type IV Osteogenesis Imperfecta; established by a substitution within the gene of the alpha-1 chain of Type I collagen. This model provides a reproducible system in which to study the role of subchondral bone in age related, degenerative arthritis. This study utilizes micro-MRI and micro-CT, as well as histological correlation to detect the changes in both the bone and cartilage of knee joints within OI mice and their age matched wild type controls. The preliminary results of our study confirm a more prominent, age related decrease in the integrity of the articular surface, with narrowing of the joint space and progressive subchondral cyst formation and extra-articular ossification evident within the OI strains. These initial results provide evidence to suggest an imporant role of bone in the early pathogenesis of primary osteoarthritis. In addition, these results also support the promising use of our OI mouse model as a unique in vivo and in vitro system for investigating the role of subchondral bone in OA.